PROFILE LYMPHOCYTES BASED ON INTAKE OF VITAMIN A IN PATIENTS WITH BREAST CANCER - Hapsari Sulistya Kusuma; Yunan Kholifatudin Sya'di (Universitas Muhammadiyah Semarang, 2017)
Cancer is the 4th leading cause of death in Indonesia for non infectious diseases. The risk of all types of cancer can be lowered by increasing the consumption of vegetables rich in carotene (Vitamin A). Cancer patients in Indonesia estimated 1.02 million people and the prevalence of cancer patients in hospitals Tugurejo Semarang in 2015 was 2.39%. Objective to determine the relationship of vitamin A with levels of lymphocytes of breast cancer patients. This research is explanatory research with cross sectional approach, in hospitals Tugurejo Semarang in July 2016. The population is breast cancer patients in the wards in hospitals Tugurejo Semarang. Samples were taken based on inclusion criteria (11 people). The analysis used is the Pearson Test. The mean age of respondents was 45.9 7.8 years. The mean body mass index of respondents was 21.16 4.11 kg / m2. The mean serum albumin level was 3.44 0.985 g / dl. The mean levels of lymphocyte is 1,51x103 0,71x103 / mm3 most respondents have less lymphocyte levels were 9 people (81.81%). The mean intake of vitamin A is 1053.8 689.7 g most respondents have a good intake level of 8 people (72.72%). No statistically significant association with the intake of vitamin A levels of lymphocytes (p = 0.853). There is no relationship between intake of vitamin A with lymphocytes in breast cancer patients. Keywords: vitamin A, lymphocytes, breast cancer